Immunogenicity and protective efficacy of OmpA subunit vaccine against Aeromonas hydrophila infection in Megalobrama amblycephala: An effective alternative to the inactivated vaccine - Zhang, Minying; Zhang, Ting; He, Yang; Cui, Hujun; Li, Hong; Xu, Zehua; Wang, Xu; Liu, Yunlong; Li, Hongping; Zhao, Xiaoheng; Cheng, Hanliang; Xu, Jianhe; et al. (Frontiers in Immunology, 2023)
Aeromonas hydrophila is a kind of zoonotic pathogen, which can cause bacterial septicemia in fish and bring huge economic losses to global aquaculture. To evaluate the immune protective effects of inactivated vaccine and recombinant outer membrane protein A (OmpA) subunit vaccine against A. hydrophila in juvenile Megalobrama amblycephala, the present study investigated the cumulative mortality rate and bacterial load in vaccinated and non-vaccinated M. amblycephala post A. hydrophila infection, as well as the immunogenicity of various vaccines, and the nonspecific and specific immune responses of M. amblycephala. The results showed that both inactivated and OmpA subunit vaccines improved the survival rates of M. amblycephala upon infection, compared to that of the non-vaccinated group, and the protective effects of the OmpA groups were better than that of the inactivated vaccine groups, which should be attributed to the reduced bacterial load and enhanced host immunity in the vaccinated fish. ELISA assay showed that the titer of serum immunoglobulin M (IgM) specific to A. hydrophila up-regulated significantly in the OmpA subunit vaccine groups at 14 d post infection (dpi), which should contribute to better immune protective effects. In addition, vaccination enhanced host bactericidal abilities might also attribute to the regulation of the activities of hepatic and serum antimicrobial enzymes. Moreover, the expression of immune-related genes (SAA, iNOS, IL-1 β, IL-6, IL-10, TNF α, C3, MHC I, MHC II, CD4, CD8, TCR α, IgM, IgD and IgZ) increased in all groups post infection, which was more significant in the vaccinated groups. Furthermore, the number of immunopositive cells exhibiting different epitopes (CD8, IgM, IgD and IgZ) that detected by immunohistochemical assay had increased in the vaccinated groups post infection. Thus, host immune responses of the vaccinated fish (especially the OmpA vaccine groups) were stronger than the that of the non-vaccinated fish. In conclusion, these results indicated that both the inactivated vaccine and OmpA subunit vaccine could protect juvenile M. amblycephala against A. hydrophila infection, of which OmpA subunit vaccine provided more effective immune protection and can be used as an ideal candidate for the A. hydrophila vaccine.